Resolution Limits of Continuous Phase Filters beyond the Diffraction Limit (Global Journal of Science Frontier Research, 2012)
Based on the series of figures of merit, we have designed the superresolution phaseonly pupil filters to control the irradiance distribution in the focal region of an optical system. The performance of these filters has been examined in terms of two point resolution by applying modified Sparrow criterion. It is observed that the presence of these pupil functions enhancing the resolution of an optical system beyond the diffraction limit.
Keywords: phase 2013; pupil; superresolution; degree of coherence; intensity ratio; sparrow limit; FWHM